Travel choice reframed: "deep distribution" and gender in urban transport. (April 2013) - Levy, Caren
Transport is a critical system in the city, which, through providing access to essential activities, enables diverse women and men, girls and boys to "appropriate" their right to the city and to realize a fully rounded and substantive urban citizenship. Yet, despite decades of work on gender in urban development and urban planning, mainstream transport planning still remains largely untouched by debates on diversity and difference in cities. The tendency to focus on the economic and now environmental aspects continues to dominate urban transport. In contrast, concerns for the identity of urban residents or "users" are addressed through, and ultimately marginalized to, "the social" and distributional aspects of urban transport planning. This paper argues that the distributional aspects of transport are cross cutting, and go beyond the disaggregation of transport users by social relations such as class, gender, age and ethnicity. The social identities of transport "users" are deeply embedded in social relations and urban practices, the latter ranging from the everyday lives of people to urban policies and planning. Furthermore, in transport, these social relations are played out in public space, with implications for how diverse women and men, girls and boys are able to exercise individual and collective "travel choice" and negotiate access to essential activities in the city. Recognition of these processes, as reflected in the "deep distribution" of the transport system, is essential to reframing the notion of "travel choice" and, ultimately, to urban transport and urban planning that is committed to social justice in cities.